Religious identity in the workplace: A systematic review, research agenda, and practical implications - Héliot, YingFei; Gleibs, Ilka H.; Coyle, Adrian; Rousseau, Denise M.; Rojon, Céline (Human Resource Management, 2020)
AbstractWe conducted a systematic review of relevant literature to address how religious and occupational identities relate to each other in the workplace. We identified 53 relevant publications for analysis and synthesis. Studies addressed value differences associated with religion and occupation, identity tensions, unmet expectations, and the connection of religious identity to well‐being and work outcomes. Key variables in the connection between religious and occupational identities included personal preferences, the fit between religious identity and job‐related concerns, and the organization's policies, practices, and expectations. We highlight the personal and organizational consequences of being able to express religious identity at work and the conditions that promote high congruence between religious identity and its expression in the workplace. From these findings, we develop a research agenda and offer recommendations for management practice that focus on support for expression of religious identity at work while maintaining a broader climate of inclusion.